Peningkatan Literasi Keluarga dalam Konten Edukatif Pembuatan Brownies Kukus Melalui Youtube - Riza, Muhammad Fathur; Nikmah, Naelan; Hidayah, Siti Nela Lailatul; Anggraeni, Vania Dhea; Jannah, Ro’I Khatul; Afiyah, Nor; Malichatin, Hanik (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2021)
YouTube is an online video site that provides a variety of information in the form of moving and reliable images. Many users access YouTube to find out how to do certain things, such as cooking demos, how to use applications in a computer or smartphone, recycle garbage, practical ways to do things that are initially complicated or ineffective, hone various skills and so on. This is a descriptive qualitative research employing non probability technique, a type of snowball sampling. The ingredients used for making brownies are eggs, baking soda, vanilla, sugar, wheat flour, cocoa powder, oil and water. In the process of steaming the brownies, heat transfer occurs in the form of conduction, convection and radiation and chemical changes also occur in brownies dough into well-cooked brownies cake. This research aims to find out to what extent the family knowledge in using YouTube as a source of information on science in the kitchen. The results obtained by YouTube can easily be accessed by the public. It is also often used by the public to look for recipes because there is a detailed explanation. After watching the video about brownies making, the insights gained about science in the kitchen increased.